Development of fuzzy logic controller for DC-DC converter in electric vehicle - Saripudin M.; Mansor M. (Praise Worthy Prize S.r.l, 2023)
This paper presents a power converter for an electric vehicle (EV) as a battery charger. An isolated DC-DC converter topology is used in order to convert the high voltage in the main battery (96V), to low voltage (12V) which is an auxiliary battery for use to power up standard accessories in EV. Many topologies have been proposed for such applications. In this paper, an isolated current-fed full bridge buck converter with a combination of fuzzy logic controller (FLC) and PWM voltage mode controller is proposed. Being free of complex equations and heavy computations, the controller is expected to control converters that operate at high frequencies. Finally, the converter circuit is simulated in MATLAB/Simulink to verify the performance of the closed-loop control of the power converter in respect of start-up transient, load regulation, reference voltage, Vref variation and line regulation. © 2014 Praise Worthy Prize S.r.l. - All rights reserved.